Performance of Two-Area Interconnected Power System with High Wind Power Penetration in Presence of Plug-in Hybrid Electric Vehicles - Harby, Mahmoud Essam; Elmasry, Said Elsayed; Elsamahy, Adel; Marroyo, Luis; Marcos, Javier (European Scientific Journal, ESJ, 2018)
Most of existing power grids are designed neither by latest technologies nor to comply with quickly climate changes, the new intelligent power grids are urgently needed and will soon be applied to the power markets. In the smart grid, the large-scale renewable energy contribution tends to expand vastly. This paper is focusing on the wind energy. Wind’s inherent intermittency and unpredictability make its increased penetration into the power system grids an area requiring significant analysis and research. Notwithstanding, because of the changeable nature of the wind energy, this may lead to a high oscillation on the power system frequency. From another aspect, A lot of scientific research is searching for smart solutions and tools to support and enhance the integration of the renewable energy resources into the electrical grids without additional costs for the power system, so the world scientific research is directed to exploit the plugin hybrid electric vehicles (PHEVs) which are considered as the sustainable and environmental friendly transportation system in the next period around the world. PHEVs are considered as the scattered batteries, which will enhance the integrating of the renewable energy resources into the electrical power system. In this paper, the performance of two-area interconnected power system with high wind energy penetration is analyzed in the presence of the plug-in hybrid electric vehicles when using Ziegler and Nicholas method (Nguyen & Mitra, 2018).